KEPRAKTISAN DAN EFEKTIVITAS MEDIA KOMIK BERGAMBAR PADA MATA PELAJARAN PPKN MATERI KEWAJIBAN DAN HAK KELAS III SDN PETUNGROTO - Rahayu, Indriati; Nurmilawati, Mumun; Santi, Novi Nitya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low learning outcomes of third grade students in PPKn subjects at SDN Petungroto, with an average score of 73.73% and there are still students who have not reached the KKM. This is due to limited learning media, less conducive classroom conditions, and low student enthusiasm in learning. This study aims to test the practicality and effectiveness of learning media in the form of illustrated comics in PPKn subjects. The method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of this study were 20 third grade students of SDN Petungroto, with data collection techniques in the form of questionnaires, interviews, and tests. The results of the study showed that the practicality of this media was very high, with a percentage of teacher response questionnaires of 84% and student response questionnaires of 96%. In addition, the post-test results showed the effectiveness of the media with an average percentage of 88.3%. Thus, it can be concluded that the developed illustrated comic media has proven to be practical and effective, so it is suitable for use in the PPKn learning process for grade III.